Stress analysis on short flat bar with projection using boundary element method - Lim, Wei Sheng (2019)
Mechanical components such as short flat bars with projections are usually used to transmit axial, shear and bending loads. Geometrical discontinuities such as sharp edges or fillet are found in attaching the head and shank part within the components. Local stress at this critical region is observed to be higher than others regions due to the abrupt changes in cross-sectional area. Cracks initiation and propagation are more likely to occur around the region of stress concentration and eventually result in mechanical failure. Hence, a detailed stress analysis on such component must be performed to prevent the failure from occurring during its working lifetime. In this project, a BEM based computational program, BIE2DS version 2B was applied in study the stress analysis on T-bar projection through determining the nodal stress concentration factor, SCF. The model of T-bar projection will be meshed and designed with the application of axial and shear loading under remote and local restraints. SCF distribution profiles for different cases were presented to find out the location of maximum SCF. Effects on SCF due to various ratios of geometrical parameters were also presented in graph for further discussion. The computational results obtained were compared with the published results done by S.J. Hardy and M.K. Pipelzadeh, and they are found in good agreement. From the result, the SCF is found out to be peaked within the region of middle point on the fillet to the fillet-to-shank intersection point. The results had shown that by increasing the radius of the fillet on T-bar projection, the value of SCF will be reduced significantly.